The Effectiveness of Restorative Justice in Resolving Juvenile Criminal Cases: An Examination of Legal and Social Perspectives - Karina, Ica (Jurnal Smart Hukum (JSH), 2024)
The objective of this research is to examine and address issues pertaining to the enforcement of the law in instances of violent criminal activity perpetrated by students of legal age who are enrolled in educational institutions. External factors, including association, education, and social environment, exert a significant influence on children's criminal behavior, which frequently originates from the tendency to emulate negative behaviors and the lack of adequate parental supervision. This research employs a normative legal approach to elucidate the nature of the penalties imposed upon minors who perpetrate criminal acts, as delineated in the Juvenile Criminal Justice System No. 11/2012. The findings indicate that to avert criminal conduct by minors, it is imperative to implement sustainable development initiatives that bolster the survival, physical, mental, and social advancement of children, while safeguarding them from threats that could jeopardize their future and the nation. The juvenile criminal justice system incorporates community involvement throughout the entirety of the case process. Crimes occurring within the community are shaped by the prevailing social conditions, along with individual factors pertaining to the perpetrators and victims. At the conclusion of each case, the community is tasked with facilitating the reintegration of offenders and victims back into the social milieu. This is achieved through either the establishment of new informal institutions or the reinforcement of existing formal ones.